Penerapan Fungsi Manajerial dalam Perspektif Geografi Pertanian di Wilayah Komunitas Suku Bayan, Kabupaten Lombok Utara, Nusa Tenggara Barat - Raihan Budiputra, Aqshal (Green Publisher Indonesia, 2025)
Managerial functions involve decision-making, interpersonal relationships and information transfer based on four basic management functions, namely planning, organizing, actuating, and controlling. These four functions are implemented using strategic management decision-making tools in the form of strengths, weaknesses, opportunities, and threats analysis or SWOT (Strengths, Weaknesses, Opportunities, & Threats) analysis. Managerial functions involve decision-making, interpersonal relationships, and information transfer based on the four basic functions of management, namely planning, organizing, actuating, and controlling. The four functions are implemented using strategic management decision-making tools in the form of strengths, weaknesses, opportunities, and threats analysis or SWOT (Strength, Weakness, Opportunity, & Threats) analysis. This study uses a literature review method based on descriptive qualitative analysis by adding narrative elements to delve deeper into the dynamics of the agricultural system in the region. This study aims to formulate concrete steps that can improve the agricultural system in the Bayan Tribe Community Area, taking into account the factors present in the SWOT analysis. The results show the importance of implementing a more structured and culture-based managerial function, as well as offering solutions that can improve the efficiency and sustainability of agriculture in the region. This research is expected to provide insights for local culture-based agricultural management and contribute to the development of managerial strategies in the agricultural sector in customary territories.